2019
DOI: 10.3390/microorganisms7080253
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Aspergillus flavus in Ensiled Sorghum by Water Kefir Microorganisms

Abstract: The capacity of microorganisms from water kefir (WK) to control Aspergillus flavus growth during the aerobic phase of ensiled sorghum grains was determined. Sorghum inoculated with A. flavus was treated with filter-sterilized and non-sterilized water kefir, ensiled, and incubated 7 days at 25 °C. A. flavus growth was quantified by qPCR after incubation. Mold growth was inhibited in the presence of water kefir while no inhibition was observed when filter-sterilized water kefir was applied, demonstrating the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…The fungal population was mainly composed of the yeasts Saccharomyces and Kazachstania, but with a higher abundance of Bionectriaceae in some samples of LB + LH silages. Bionectriaceae has rarely been reported in corn silage but has been observed in sorghum before ensiling (Gonda et al, 2019). Interestingly, in this family,…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The fungal population was mainly composed of the yeasts Saccharomyces and Kazachstania, but with a higher abundance of Bionectriaceae in some samples of LB + LH silages. Bionectriaceae has rarely been reported in corn silage but has been observed in sorghum before ensiling (Gonda et al, 2019). Interestingly, in this family,…”
Section: Discussionmentioning
confidence: 82%
“…The fungal population was mainly composed of the yeasts Saccharomyces and Kazachstania , but with a higher abundance of Bionectriaceae in some samples of LB + LH silages. Bionectriaceae has rarely been reported in corn silage but has been observed in sorghum before ensiling (Gonda et al, 2019). Interestingly, in this family, the Clonostachys related‐OTU is an epiphytic mycoparasitic fungus that can be used for biocontrol of Fusarium graminearum (Gimeno et al, 2019), and also has the enzymatic potential to degrade zearalenone (Ogunade et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Kefir grains are complex biological entities comprising diverse species of microorganisms) that have been used for centuries to create fermented drink products from either milk or water. More recently, studies have shown that the microorganisms present in probiotic water kefir have a capacity to act biocontrol agents in stored grains [38]. Utilizing such consortia, or the organisms within them, for postharvest biocontrol, would represent a novel approach to providing both decay control and a source of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Kefir has also received considerable scholarly attention in recent years due to its antioxidant, anti-inflammatory, antifungal, antibacterial specialties, and various pharmaceutical attributes [12][13][14]. Previous research evaluating the effect of kefir microorganisms on aerobic spoilage of sorghum and wheat-straw silages also strengthens these assumptions [15,16]. However, there is a notable lack of high-quality research focusing specifically on fermentation characteristics, aerobic stability, and the microbial community of alfalfa silages inoculated with different kefir sources.…”
Section: Introductionmentioning
confidence: 99%